Kinerja Sekolah dalam Implementasi Merdeka Belajar (Studi di SMP Negeri 5 Satu Atap Sitellu Tali Urang Jehe Pakpak Bharat) - Manullang, Juni Merry Ria; Amini, Amini; Isman, Muhammad (UMSU, 2024)
The purpose of this research is to Find out the performance of schools in implementing Independent Learning at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat, and Knowing the Obstacles to School Performance in Implementing Freedom of Learning at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat. 3) Knowing the Solution to Overcoming School Performance in the Implementation of Independent Learning at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat. The research method is a qualitative. The data analysis technique in this research is qualitative data analysis. Data collection techniques using interviews, documentation and observation. The results of this research are: 1) The school's performance in implementing the Independent Learning curriculum at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat has not been optimal because some teachers have not been able to adapt to the Independent Learning curriculum, teaching modules are available but the implementation of differentiated learning has not been found even though the school principal has designed all socialization activities, teachers have also implemented the Independent Learning curriculum at school. 2) Obstacles to school performance in implementing the Merdeka curriculum for learning at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat are incomplete facilities and infrastructure, then a lack of socialization and assistance to the Merdeka curriculum for teachers, then a lack of teacher pedagogical ability in implementing the curriculum Freedom to learn, especially related to P5. The solution to overcoming school performance in the implementation of Freedom to Learn at SMP Negeri 5 One Roof Sitellu Tali Urang Jehe Pakpak Bharat is that teachers must be united and motivate themselves to further upgrade their abilities, teachers need training, assistance with the Merdeka learning curriculum and facilities and Infrastructure needs to be equipped so that the teaching and learning process runs well.